2020
DOI: 10.1177/1558944720939198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trapeziectomy on Carpal Stability

Abstract: Background: The scaphoid-trapezoid-trapezium (STT) articulation stabilizes the scaphoid and links the proximal and distal carpal rows. The purpose of the study was to determine whether trapezium excision in the treatment of trapeziometacarpal (TM) arthritis affects carpal stability. Methods: A retrospective chart and radiographic review was performed on all wrists that underwent trapeziectomy with suspensionplasty or ligament reconstruction, and tendon interposition for TM arthritis between 2004 and 2016. Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…In contrast, a study that reviewed radiographs from 22 patients before and at mean of 8.5 months after trapeziectomy/LRTI reported a significant increase in number of wrists with abnormal scapholunate angle from 32% before to 55% after surgery [ 6 ]. In a study of 122 wrists examined before and at a mean of 3.5 (1–13) years after trapeziectomy/LRTI, the authors suggested increased risk of developing non-dissociative carpal instability patterns after trapeziectomy [ 4 ]. In a previous report of two cases of carpal collapse after trapeziectomy and partial trapezoid resection, the authors suggested that carpal collapse may more likely occur after trapeziectomy with simultaneous partial trapezoidectomy than after trapeziectomy alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study that reviewed radiographs from 22 patients before and at mean of 8.5 months after trapeziectomy/LRTI reported a significant increase in number of wrists with abnormal scapholunate angle from 32% before to 55% after surgery [ 6 ]. In a study of 122 wrists examined before and at a mean of 3.5 (1–13) years after trapeziectomy/LRTI, the authors suggested increased risk of developing non-dissociative carpal instability patterns after trapeziectomy [ 4 ]. In a previous report of two cases of carpal collapse after trapeziectomy and partial trapezoid resection, the authors suggested that carpal collapse may more likely occur after trapeziectomy with simultaneous partial trapezoidectomy than after trapeziectomy alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, trapeziectomy with LRTI is one of the most common procedures used for treating TMC OA [ 2 ]. Trapeziectomy partly disrupts the constrains of the scaphotrapeziotrapeziod (STT) joint, which has been suggested to potentially cause a carpal instability pattern that has been termed as non-dissociative [ 4 6 ]. Non-dissociative carpal instability is defined as a kinematic dysfunction of the entire proximal carpal row, manifested as either an instability between the proximal and distal rows, or between the proximal row and the radius [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no consensus on the impact of resection of the trapezium on carpal stability ( 17 , 18 ), recent publications concluded that trapeziectomy can lead to a loss of carpal height with extension of both the lunate and scaphoid and a non-dissociative pattern of dorsal intercalated segment instability (DISI) ( 19 , 20 ). This explains why patients with preoperative DISI deformity of the carpus have a significantly higher chance to be dissatisfied after trapeziectomy than patients without preoperative DISI ( 21 ).…”
Section: Rationale For Total Joint Replacementmentioning
confidence: 99%
“…Removal of the trapezium can lead to progressive arthrosis in the remaining articulation between the scaphoid and the trapezoid ( 19 , 20 , 21 ).…”
Section: Rationale For Total Joint Replacementmentioning
confidence: 99%
“…Studies have shown that trapeziectomy can lead to midcarpal instability and a loss of carpal height. [5,6] When a trapeziectomy is performed in patients with a preopera tive DISI deformity there is a higher chance of dissatisfaction [7] whereas a total joint arthroplasty will preserve the trapezium with out further destabilization of the wrist.…”
Section: Patient Evaluationmentioning
confidence: 99%